Mathematical methods for cell cycle analysis from flow cytometric DNA-BrdUrd distributions - Bertuzzi, Alessandro; Gandolfi, Alberto; Sinisgalli, Carmela; Starace, Giuseppe (Zielona Góra: Uniwersytet Zielonogórski)
The paper discusses some mathematical methods, presented in the literature or proposed by the authors, which aim at the estimation of cell kinetic parameters from DNA-BrdUrd distributions obtained by the pulse labelling technique. In particular, we give an expression for the time behaviour of the relative movement of BrdUrd-labelled undivided cells, that takes into account the variability of DNA synthesis rate across S phase.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka